A Multicriteria Decision Support System for Used Smartphone Price Determination Using CRITIC–MARCOS - Laili Fitriyani; Anteng Widodo; Yudie Irawan (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
Used smartphone price determination at FS Phone Store Jepara has relied mainly on the seller’s subjective judgment, resulting in inconsistent valuation across units with comparable specifications and condition. This study developed a multicriteria decision support model that integrates the Criteria Importance Through Intercriteria Correlation (CRITIC) method for objective criteria weighting with the Measurement of Alternatives and Ranking according to Compromise Solution (MARCOS) method for alternative ranking, applied to 100 used smartphone alternatives evaluated on nine criteria: physical condition, RAM, ROM, chipset, camera, battery health, usage age, warranty, and completeness. To align the technical assessment with real market conditions, a market-price correction (85% MARCOS utility score plus 15% normalized market-price score) was applied to the final ranking. The proposed ranking was compared with Weighted Product (WP), MOORA, and Simple Additive Weighting (SAW) using Spearman rank correlation, and the accuracy of the resulting price recommendation was evaluated against an Independent Market Reference Price using Mean Absolute Error (MAE) and Mean Absolute Percentage Error (MAPE). The results show that Usage Age obtained the highest CRITIC weight (21.12%) and Camera the lowest (8.22%). The final price-corrected ranking achieved a strong to very strong correlation with SAW (rₛ = 0.9291), WP (rₛ = 0.8015), and MOORA (rₛ = 0.8256), and produced price recommendations with an MAE of IDR 90,600 and a MAPE of 4.63%, classified as highly accurate. The proposed model was implemented as a web-based decision support system, validated through black-box testing, user acceptance testing, and manual calculation verification, providing FS Phone Store Jepara with an objective, consistent, and market-aware tool for used smartphone price determination.